Membangun Resiliensi UMKM Melalui Peran Digitalisasi dan Praktek Sumber Daya Manusia - Muharam, Husni; Kurniawan, Deri Alan; Rosita, Iis; Rahman, Riqki Taufik (Universitas Bunda Mulia, 2024)
Changes in the current digital era occur very quickly and lead to conditions that continue to change dynamically, so overcoming the increasing uncertainty in the organization becomes important and urgent for an organization and the organization's ability to develop resilience is also very necessary. MSMEs face various challenges in the digital era, such as changes in consumer behavior, global competition, and economic uncertainty. These conditions have prompted several previous studies that focus on organizational resilience, which is interesting because all organizations need to survive and recover after facing difficulties and challenges. The resilience of MSMEs is the main determinant to overcome this uncertainty, by understanding how digitalization and HR can complement each other to create excellence. This study aims to determine how digitalization and human resources affect resilience (Study on MSME at Car Free Day Jalan Ibrahim Adjie Garut Regency) The research method used is quantitative with a descriptive approach. Primary data was obtained by distributing questionnaires to 80 respondents using the random sampling method. The data analysis technique used in this study used PLS-SEM. The results of the analysis show that the role of digitalization does not have a significant effect on resilience, but on the contrary, the practice of human resources proves the results that have a significant effect on resilience.